2002
DOI: 10.1046/j.1365-232x.2002.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing construction supply chains: the common sense approach

Abstract: This paper will provide an introduction to the argument that there is considerable evidence of poor thinking within the construction industry. The failure to understand the circumstances that are facing industry players will prevent clients, contractors and suppliers from achieving their own objectives. The current problems are further compounded by the advice espoused by the government‐sponsored industry reports advocating generic approaches. In response to these problems the paper will provide practitioners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 17 publications
0
64
0
Order By: Relevance
“…Drawing upon the framework of Lambert et al (1996), the partnerships focused on time investment for joint BIM learning during the project, rather than investment in tangible assets, such as acquiring technology or hiring specialized personnel. Such proactive behaviour towards developing their partners could not only facilitate relationship management, but also encourage innovation (Cox & Ireland, 2002). Regarding the timing of BIM adoption, no disruption effects were observed in the older partnership (case B), because BIM implementation used pre-existing communication channels, while the 'newer' case A had to implement both digital and relational changes simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing upon the framework of Lambert et al (1996), the partnerships focused on time investment for joint BIM learning during the project, rather than investment in tangible assets, such as acquiring technology or hiring specialized personnel. Such proactive behaviour towards developing their partners could not only facilitate relationship management, but also encourage innovation (Cox & Ireland, 2002). Regarding the timing of BIM adoption, no disruption effects were observed in the older partnership (case B), because BIM implementation used pre-existing communication channels, while the 'newer' case A had to implement both digital and relational changes simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of construction integration persists across its lifecycle and involved actors (Briscoe & Dainty, 2005;Fernie & Tennant, 2013;Nam & Tatum, 1992), due to the conflicting nature of demand and supply (Cox & Ireland, 2002). Integration pertains to both processes and actors, and regarding the latter as collaboration across tiers (Dulaimi, Ling, Ofori, & De Silva, 2002).…”
Section: Synthesis Of Sc Partnering and Bim For Integrationmentioning
confidence: 99%
“…These factors have been suggested as the "root causes" of observed problems (Cox and Ireland, 2002) including lack of coordination and communication between participants,…”
Section: Introductionmentioning
confidence: 99%
“…The construction industry is a major one: in most national economies it accounts for between 6% and 10% of the gross domestic product. The industry is fragmented and its culture is predominantly adversarial (Cox and Ireland, 2002). Most construction firms operate in a decentralized network of suppliers (subcontractors, material suppliers, service suppliers etc.)…”
Section: Context Of the Construction Industrymentioning
confidence: 99%
“…Arbulu et al (2003) found inefficiencies at the interfaces between processes, disciplines and organisations in a construction supply chain. Cox and Ireland (2002) identified circumstances under which an integrated supply chain approach could be successfully implemented in a supplier-contractor relationship. Davidson (2009) argues for an upfront organisational design (alongside a technical design) for contemporary manufacturing innovators in the construction industry.…”
Section: Common Research Subjects Theoretical Approaches and Tools Usedmentioning
confidence: 99%